2012
DOI: 10.1098/rstb.2012.0232
|View full text |Cite
|
Sign up to set email alerts
|

Climate change in size-structured ecosystems

Abstract: One important aspect of climate change is the increase in average temperature, which will not only have direct physiological effects on all species but also indirectly modifies abundances, interaction strengths, food-web topologies, community stability and functioning. In this theme issue, we highlight a novel pathway through which warming indirectly affects ecological communities: by changing their size structure (i.e. the body-size distributions). Warming can shift these distributions towards dominance of sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
175
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(185 citation statements)
references
References 91 publications
8
175
0
2
Order By: Relevance
“…However, changes in interaction strengths will be different between source and sink communities if large-bodied species migrate preferentially ( figure 1c,d). This is based on the scaling of predator-prey interaction strengths with predator : prey body size ratios-the larger the difference in size between predators and prey, the larger their interaction strength [10]. If large-bodied species from high trophic levels and large individuals within a species preferentially migrate, then interaction strengths in the source community would become weaker (loss of large predator : prey size ratios; figure 1c in blue) and they would become stronger in the sink community (gain of large predator : prey size ratios; figure 1d in blue).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, changes in interaction strengths will be different between source and sink communities if large-bodied species migrate preferentially ( figure 1c,d). This is based on the scaling of predator-prey interaction strengths with predator : prey body size ratios-the larger the difference in size between predators and prey, the larger their interaction strength [10]. If large-bodied species from high trophic levels and large individuals within a species preferentially migrate, then interaction strengths in the source community would become weaker (loss of large predator : prey size ratios; figure 1c in blue) and they would become stronger in the sink community (gain of large predator : prey size ratios; figure 1d in blue).…”
Section: Discussionmentioning
confidence: 99%
“…It is also a trait known to affect a number of biological processes, from the individual to the ecosystem level, including metabolism, fecundity, population growth rate, population density, trophic flows or ecosystem respiration [8,9]. Within trophic interaction networks, a number of studies have reported that body size determines food web structure and dynamics (see [10] for a review). For example, large predators tend to interact with more diverse prey items than smaller ones, and predator : prey size ratios determine biomass flux and interaction strength, ultimately regulating food web dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can potentially exaggerate the negative effects of climate change. Climate change is likely to have profound and complex effects on local as well as global ecological communities [40], which highlights the importance of analyses including both scales. Here we analyse how increased mortality during species dispersal affects the robustness of metacommunities, both in isolation and in concert with additional disturbances (local species extinctions).…”
Section: Discussionmentioning
confidence: 99%
“…Climate warming is known to alter herbivore population growth [16] in addition to affecting individual body size [17] and metabolic process rates [18], and these changes may combine to affect foodweb interactions through a variety of pathways [19]. Similarly, nitrogen deposition is known to alter plant quality, with cascading effects on herbivore individual fitness and population growth [13].…”
Section: Introductionmentioning
confidence: 99%